Measured Tones: The Place of People of Colour in Norwegian Reading Lists - Andrew Thomas; Sandra Fylkesnes (Nordisk tidsskrift for pedagogikk og kritikk)
What do Norwegian reading lists in pedagogy in postgraduate teacher-training communicate about race? A content analysis of all reading lists for modules in pedagogy that form part of the Norwegian postgraduate certificate of education and were posted online in autumn 2021 coded 0.2% (75 of the 35,116) of the pages as authored by people of colour; about one in every twenty pages pertained to people of colour and almost all the contributions by authors coded as people of colour concerned people of colour. Compared to statistics regarding students taking these courses that year, people of colour are not only invisible in these reading lists, but their visibility is primarily as an educational concern and only secondarily as intellectual agents. Although reading lists in education communicate concern about people of colour, they do not communicate trust in them as fellow academics.